Control estadístico de los indicadores de calidad de calzado plástico - Vélez Suárez, Erika Pamela (2010)
The present study develops statistical quality control (SPC) of percentage of calcium carbonate and thickness of PVC boots. The latter characteristics are key indicators on the preparation of PVC boots. SPC is used to determine assignable causes of variation in the process. Afterwards, the levels of the key indicators are improved. The methodology consists of process mapping, selection of critical quality indicators, statistical quality control of the process, process capability analysis and cost estimation. The analysis compares the costs of the current process with the costs of the process under statistical control. This study makes clear the cost reduction and quality improvement when the SPC is applied to the finished product.